How Pupuhu Adat as guardians of spirituality and indigenous leadership in Indonesia? A Case Study from Sunda Wiwitan Community - Rakhmat Hidayat; Muhammad Ilman Naafi'a; Dimas Wira Aditama (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
This paper examines indigenous leadership within the Sunda Wiwitan community, focusing on Susuru Hamlet in Kertajaya Village, Ciamis Regency. Indigenous leadership plays a crucial role in ensuring the survival of indigenous groups in Indonesia, particularly within Sunda Wiwitan, where leadership is deeply embedded in cultural and spiritual traditions.In this community, the highest leader is the Pangeran (Prince), a position currently held by Prince Gumirat Barna Alam. As the traditional leader, the Pangeran’s authority extends across various Sunda Wiwitan communities in West Java. The Pangeran is also recognized as the Pupuhu Adat, a title attributed to the community’s spiritual and cultural leader.The role of the Pupuhu Adat includes guiding collective decision-making, preserving cultural traditions, and providing spiritual leadership. Leadership is inherited hereditarily rather than determined through electoral processes, with consensus-based decision-making being highly valued. The Pupuhu Adat serves as the custodian of ancestral wisdom and traditions, ensuring the continuity and cohesion of the Sunda Wiwitan community.